Adapting Simple Index-Based Catch Rules for Data-Limited Stocks to Short-Lived Fish Stocks’ Characteristics - Sánchez-Maroño, Sonia; Uriarte, Andrés; Ibaibarriaga, Leire; Citores, Leire (Frontiers in Marine Science, 2021)
Most of the methods developed for managing data-limited stocks have been designed for long-lived species and result in a poor performance when applied to short-lived fish due to their high interannual variability of stock size (IAV). We evaluate the performance of several catch rules in managing two typical short-lived fish (anchovy-like: characterized by high natural mortality, and hence, IAV, and full maturity at age 1; and sprat/sardine-like: with medium natural mortality and IAV, being fully mature at age 2). We followed the management strategy evaluation approach implemented in FLBEIA software to test several model-free harvest control rules, where the Total Allowable Catch (TAC)is yearly modified according to the recent trends in an abundance index (n-over-m rules: means of the most recent n values over the precedent m ones). The performance of these rules was assessed across a range of settings, such as time-lags between the index availability and management implementation, and alternative restrictions on TACs’ interannual variability (the uncertainty caps, UC). Moreover, we evaluated the sensitivity of the rule performance to the operating model assumptions (stock type, productivity, recruitment variability and initial depletion level) and to the observation error of the index. In general, the shorter the lag between observations, advice and management, the bigger the catches and the smaller the biological risks. For in-year management, 1-over-m rules are reactive enough to stock fluctuations as to gradually reduce risks. The 1-over-2 rule with symmetric 80% UCs reduces catches and risks towards precautionary levels in about 10 years, faster than if applied unconstrained (i.e., without UC), whilst the ICES default 2-over-3 rule with symmetric 20% UC is not precautionary. We prove that unconstrained rules gradually reduce the fishing opportunities, with amplified effects with increasing IAV. This property explains the stronger reductions of catches and risks achieved for the anchovy compared to the sprat/sardine-like stocks for any rule and the balance between catches and risks as the index CV increases. However, to avoid unnecessary long-term losses of catches from such reduction properties, it is suggested that the rules should be applied provisionally until a better assessment and management system is set up.